IMMEDIATE EFFECT OF KINESIO VERSUS MCCONNELL TAPING ON PATELLOFEMORAL PAIN SYNDROME DURING FUNCTIONAL ACTIVITIES- A COMPARATIVE STUDY (International Journal of Physiotherapy, 2015)
Background: Patellofemoral pain syndrome (PFPS) is a condition presenting with anterior knee pain or pain behind the patella (retro-patellar pain). The purpose of the study is to find the immediate effect of Kinesio taping versus McConnell taping in patellofemoral pain syndrome subjects during functional activities- stair ascent, stair descent and squat lift.Methods: An experimental study design with three groups, 45 subjects with patellofemoral pain syndrome was randomized. 15 subjects into each Kinesiotaping group, McConnell group and Sham group. Kinesiotaping group received patellofemoral kinesio taping technique, McConnell group received McConnell taping technique and Sham group received sham taping technique. Outcome measure pain was measured using visual analogue scale during pre and post taping pain levels that were measured during three functional activities: stair ascent, stair descent and squat lift.Results: When analysed within the group using paired ‘t’ test and wilcoxon signed rank test, there is statistically significant improvement in post pain levels in KT, MT and Sham group during stair climbing, stair descent and squat lift. When compared measuring of pre and post pain levels between three groups, there is no significant change in pain level between Kinesio taping and McConnell taping as also compared to sham taping.Conclusion: The study concluded that Kinesio taping, McConnell taping and sham taping shown immediate effect on reducing pain during functional activities such as stair climbing, stair descent and squat lift with greater percentage of pain reduction was found following Kinesiotaping and McConnell taping.